Peran Perceived Quality Pada Hubungan Credible Online Review Terhadap Purchase Intention Pada Konsumen Online Shop Gramedia Surabaya - Lavenia Fourcelia Wijaya; Krismi Budi Sienatra (Journal of Management and Social Sciences, 2023)
The research conducted by researchers has aims to be able to determine the effect of Credible Online Review on Purchase Intention mediated by Perceived Quality for online shop consumers at Gramedia Surabaya. The population used in this study were all consumers who shop using the online shop Shopee, Lazada, and Gramedia.com and know about Gramedia brands and products, and in all range age. The sampling technique, namely random sampling, was used to obtain as many as 150 samples. SmartPLS4 software is used to analyze the data. Using reflective measurement model test, formative measurement model test, R2 test, f2 test, Goodness of Fit (GOF) test, and hypothesis test and mediating effect. Questionnaires distributed via Google Form with a total of 15 question items, the assessment used was on a Likert scale of 1-5. The results obtained in this study are to determine the effect of Credible Online Review on Purchase Intention mediated by Perceived Quality for online shop consumers at Gramedia Surabaya.